(untitled) (Fiep Bulletin - online, 2013)
Currently the practice race has occupied a significant place within the physical activity programs focused on health, and people who are starting or already practiced race are increasingly seeking to improve their fitness levels. The motivations for this are varied: by concern for the physical form, is the pursuit of quality of life or simply to keep your friends corridors, the fact is that street races are increasingly gaining more fans and spaces in Brazil and abroad. The growing number of consultancies specializing in sporting street racing was a major movements observed in the last ten years. It was during this period that such rules had a "boom" in the number of participants and began to attract more and more investments, research, products and services to these communities athletes. In this sense it is necessary to draw up a work that has the objective to identify the influence of sports in advising growing road race and show the real benefits of coaching in a sport advice. To accomplish these goals, we conducted a field research, quantitative exploratory, with 60 runners street of both genders in various consultancies Fortaleza between September and November 2012. Through this research, the role of sports in advising growing street race in Brazil that aimed to identify the influence of sports staffs in the growth of street racing. Showed satisfactory results, practitioners are increasingly motivated to practice street race, noticed significant changes in lifestyle, such as improved sleep, nutrition, stress, etc..Practitioners feel safe in coaching staffs and Physical Education professionals are increasingly specializing in the area to monitor the growth.